DIGITAL TRANSFORMATION IN RURAL AREAS: A CASE STUDY OF COMPUTER TRAINING AS COMMUNITY SERVICE - Ahmad, Adi; Alfina; Rahmi Hajriyanti; Ulfah Irani Z; Eka Sri Wulandari; Syamsul Rizal (Jurnal Pengabdian Bangsa, 2024)
Digital Transformation in rural areas has emerged as a significant subject in enhancing the quality of life for local communities. This study aims to analyze the effectiveness of computer training as part of community service initiatives in implementing digital transformation. The research methodology involved structured computer training for rural residents and the evaluation of outcomes through surveys and observations. Findings indicate a significant improvement in IT literacy among participants following the training. Active engagement in this program has enhanced ICT skills within rural communities, creating potential for broader access to digital economic opportunities. In conclusion, computer training can serve as a vital tool in accelerating digital transformation in rural areas and promoting digital inclusivity in rural environments.